Perlindungan bagi Hak Perempuan Masyarakat Adat Hindu Bali dalam Hal Pewarisan - Nadia Faizah Putri Devina; Era Titis Cahya Rani; Alanda Aldora Lamandiri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Inheritance law in Indonesia has three directions, namely customary law, civil law and Islamic law. This journal article discusses one of the inheritance laws, namely customary inheritance law. The writing of this journal article aims to examine how the protection and process of obtaining inheritance rights for women in Balinese Hindu customary society, which adheres to the patrilineal system. The research method used is a normative legal research method with two approaches, namely a statutory approach and a conceptual approach. Data collection uses doctrinal which is by examining, analyzing and identifying knowledge contained in reading sources in the form of reference books, journals or previous research as research support. Based on the results of the study, it shows that under customary inheritance law, women are generally not entitled to inherit property, but only enjoy the inheritance of parents or husbands. However, they can obtain inheritance rights through grants, marital gifts (jiwa dana), or changing their status to male (sentana rajeg).